Lifestyle, Café Atmosphere, dan Customer Experience: Kunci Loyalitas Pelanggan Bento Kopi UI Depok - Giyanti Susilowati; Meylani Tuti (LPPM Universitas Asa Indonesia, 2026)
This study aims to analyze the influence of atmosphere, customer experience, and lifestyle on customer loyalty among visitors to Bento Kopi UI Depok. Customer loyalty is a crucial aspect in maintaining the sustainability of a cafe business amidst increasingly fierce competition. This study uses a descriptive quantitative method. The population in this study were consumers of Bento Kopi UI Depok using a purposive sampling technique, a technique that determines consumer criteria to be a research sample. In this study, the criteria set were consumers who have made more than two purchases. The questionnaire was distributed using Google Forms and obtained 232 respondents. The questionnaire was distributed from December 2025 to January 2026. The data analysis method used was the Structure Equation Model with the help of SmartPLS software. The results of the study indicate that atmosphere and customer experience influence customer loyalty, while lifestyle does not affect customer loyalty. This finding confirms that the creation of a comfortable atmosphere and a memorable experience is more decisive in building customer commitment to revisit and recommend customers than lifestyle suitability.